3D Printed Cabin: Housing Emergency Units - Emerging Objects (Firma) (urbanNext, 2018)
The 3D Printed Cabin brings many of Emerging Objects$1 (Bmaterial, software, and hardware experiments together to demonstrate the architectural potential of additive manufacturing on a weather tight, structurally sound building. Due to a housing emergency in the Bay Area, the Oakland City Council eased restrictions on the construction of secondary housing units, or backyard cottages. This has opened the door for Emerging Objects to use the relaxed codes to experiment towards addressing housing problems at a micro scale.s
Designing Matter, Emerging Objects, Low Density, Project, Technology and fabrication
3D printers, California, Ceramic skin, Cladding envelop, Designing Matter, Emergency architecture, Housing, Materials, Oakland, Project, USA, Vegetation
Keywords: Architecture; 3D Printing; Oakland, California, USA; USA